Practical cybersecurity fundamentals - Santos, Omar (Pearson, 2023)
12 Hours of Video Instruction Start your cybersecurity career by learning security principles and practices from cybersecurity expert Omar Santos. The Practical Cybersecurity Fundamentals LiveLessons gives you the core knowledge to start your own cybersecurity journey. This course is suitable for anyone looking to start their journey or anyone who is looking to get a security certification such as CompTIA Security+, Cisco CyberOps Associate, Certified Ethical Hacker (CEH), and GIAC Information. Omar Santos takes you on a deep dive into Cybersecurity fundamentals with a training full of demos and real-world examples that allow you to test your skills in a practical scenario. There's never been a better time to get started on your cybersecurity career! Sign up for cybersecurity live training classes by Omar Santos https://learning.oreilly.com/search/?q=omar%20santos%20cybersecurity&type=live-event-series&publishers=Pearson Topics covered include: Cybersecurity Fundamentals--Introduces the fundamental topics of security principles, business continuity (BC), disaster recovery (DR), and incident responses. This module will also cover network security and how to operate security and software defined networking including cryptography, AAA, and identity management. Incident Response, Digital Forensics, and Threat Hunting--Explores the core fundamentals of incident response, threat hunting, and digital forensics. It will teach you tactical, operational, and strategic level cyber threat intelligence skills and tradecraft required to make security teams better, threat hunting more accurate, incident response more effective, and organizations more aware of the evolving threat landscape. Ethical Hacking, Penetration Testing, and Bug Hunting--Starts with an overview of security penetration testing and bug hunting. It covers important ethical hacking topics of passive reconnaissance, OSINT, active reconnaissance, enumeration, and scanning. You will be able to conduct successful penetration testing (ethical hacking) assessments for a modern enterprise, including on-premises systems and cloud offers. Cloud, DevOps, and IoT Security--Covers cloud security concepts, DevOps, and IOT security. It provides a foundational set of standardized skills and knowledge for IoT and industrial control systems (ICS) cybersecurity professionals. You will learn foundational concepts on how to keep the ICS/SCADA/IoT operational environment safe, secure, and resilient against current and emerging cyber threats. AI Security, Ethics, and Privacy: Balancing Innovation with Protection--Introduces AI security, where you will explore LLMs, ChatGPT, Co-Pilot, and more. You will get a deep dive into different types of AI threats: data poison, model inversion, membership inference, model theft, and MITRE's ATLAS. You will also learn the principle of secure AI development. About the Instructor Omar Santos is a recognized cybersecurity thought leader with a passion for driving industry-wide initiatives to enhance the security of critical infrastructures. Omar is the chair of the Common Security Advisory Framework (CSAF) technical committee, the chair and founder of OpenEoX, and a member of the board of directors of OASIS Open and the co-lead of the DEF CON Red Team Village. Omar's collaborative efforts extend to numerous organizations, including the Forum of Incident Response and Security Teams (FIRST) and the Industry Consortium for Advancement of Security on the Internet (ICASI). Omar is a renowned expert in ethical hacking, vulnerability research, and incident response. He employs his deep understanding of these disciplines to help organizations stay ahead of emerging threats. His dedication to cybersecurity has made a significant impact on businesses, academic institutions, law enforcement agencies, and other entities striving to bolster their security measures. With more than 20 books, video courses, white papers, and technical articles under his belt, Omar's expertise is widely recognized and respected. Omar is a Distinguished Engineer leading the AI Security Research at Cisco's Security & Trust Research and Operations. Omar not only leads engineers and incident managers in investigating and resolving cybersecurity vulnerabilities, but also actively mentors the next generation of security professionals. Skill Level: Beginner Learn How To: Understand core cybersecurity fundamentals Perform ethical hacking, penetration testing and bug hunting Explore system and application including active and passive reconnaissance Understand cloud security concepts including IoT and DevSecOps Course requirement: None Who Should Take This Course: Anyone contemplating starting a career in cyber security Anyone who would like to better understand cyber security concepts Anyone studying for a security cert like CompTIA Security+, Cisco CyberOps Associate, Certified Ethical Hacker (CEH), GIAC Information About Pearson Video Training: Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que. Topics include: IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.
Online resource; title from title details screen (O'Reilly, viewed January 3, 2023)
Keywords: Computer security; Sécurité informatique; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet